Clinical Traits of SARS-CoV-2 Infection - O. Yu. Zolnikova; N. L. Dzhakhaya; N. D. Potskherashvili; K. B. Puzakov; O. Yu. Кiseleva; N. I. Kokina; E. R. Buklis; T. V. Roshchina; I. I. Коmkova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Analysis of clinical manifestations, laboratory and instrumental examination data in SARS-CoV-2 patients with taking into account the disease severity and outcome.Materials and methods. The study included 92 patients with conﬁrmed coronavirus infection, including 15 lethal cases, hospitalised at the Vasilenko Clinic of Internal Disease Propaedeutics, Gastroenterology and Hepatology of the Sechenov University in April 2020. The analysis included demographic data, the presence of concomitant diseases, chest computed tomography (CT) results, laboratory tests (including SARS-CoV-2-diagnostic PCR, general and metabolic blood panels, coagulogram) and the duration of disease.Results. Patients infected with SARS-CoV-2 usually exhibit lymphopenia (p ≤ 0.001), leucocytosis, the elevated neutrophils (p ≤ 0.05), neutrophil-lymphocyte ratio (p ≤0,05), C-reactive protein (p ≤ 0.05), ferritin (p ≤ 0.05), D-dimer (p ≤ 0.05) and ﬁbrinogen (p ≤ 0.05), altered prothrombin time (p ≤ 0.05) and INR (p ≤ 0.05). In a critical coronavirus infection, the pulmonary lesion exceeds 50% (corresponds to CT3 — CT4). The risk of critical SARS-CoV-2 infection increases with elder age (p ≤ 0.001), associates with the male gender and presence of concomitant diseases, such as obesity (p < 0.01), diabetes mellitus (p < 0.001), hypertension (p ≤ 0.001), CHD (p ≤ 0.001) and atrial ﬁbrillation (p <0.05).Conclusion. The risk of severe and adverse coronavirus infection is signiﬁcantly higher in elder comorbid patients.